Influence of Immune Cell Subtypes on Mitochondrial Measurements in Peripheral Blood Mononuclear Cells From Children with Sepsis. Issue 5 (28th May 2022) - Weiss, Scott L.; Henrickson, Sarah E.; Lindell, Robert B.; Sartori, Laura F.; Zhang, Donglan; Bush, Jenny; Farooqi, Sumera; Starr, Jonathan; Deutschman, Clifford S.; McGowan, Francis X.; Becker, Lance; Tuluc, Florin; et al.
ABSTRACT: Introduction: Peripheral blood mononuclear cells (PBMCs) are commonly used to compare mitochondrial function in patients with versus without sepsis, but how these measurements in this mixed cell population vary by composition of immune cell subtypes is not known, especially in children. We determined the effect of changing immune cell composition on PBMC mitochondrial respiration and content in children with and without sepsis. Methods: PBMC mitochondrial respiration and citrate synthase (CS) activity, a marker of mitochondrial content, were measured in 167 children with sepsis at three timepoints (day 1–2, 3–5, and 8–14) and once in 19 nonseptic controls. The proportion of lymphocytes and monocytes and T, B, and NK cells was measured using flow cytometry. More specific CD4+ and CD8+ T cell subsets were measured from 13 sepsis patients and 6 controls. Spearman's correlation and simple and mixed effects linear regression were used to determine the association of PBMC mitochondrial measures with proportion of immune cell subtypes. Results: PBMC mitochondrial respiration and CS activity were correlated with proportion of monocytes, lymphocytes, T B, and NK cells in controls, but not in sepsis patients. PBMC mitochondrial respiration was correlated with CD4+ and CD8+ T cell subsets in both groups. After controlling for differences in immune cell composition between groups using linear regression models, PBMC respiration and CS activity remained lower in sepsis patients than controls. Conclusions: Mitochondrial measurements from PBMCs varied with changes in immune cell composition in children with and without sepsis. However, differences in PBMC mitochondrial measurements between sepsis patients and controls were at least partially attributable to the effects of sepsis rather than solely an epiphenomena of variable immune cell composition.